Women Breaking into the South Korean Film World: A Study of Female Filmmakers in the 1990s - Sora Hong (Mise au Point)
In the 1990s, four women made their debut as film directors in South Korea. Considering that there were only five female directors from the beginning of Korean film history in 1919 until the 1980s, their debut was a remarkable phenomenon. This change was due to the structural innovation of the South Korean film field that began in the mid-1980s. With the collapse of the apprenticeship system, networks of cinephiles such as the Munhwawon sedae functioned as a new source of relational capital. In order to deepen our understanding of the emergence of the celluloid ceiling in South Korea, this study focuses on the experiences of three women filmmakers who made their first feature films in the 1990s: Yim Soon-rye, Lee Jeong-hyang, and Byun Young-Joo. Compared to male directors who had equivalent cultural and academic capital, and who entered the field during the same period, these women directors were unable to acquire sufficient relational capital to promote their careers as directors. It was the authorities of the field, such as film festivals and the media, that acknowledged them and established their reputations, allowing them to release their first films in the South Korean cinematic field. In other words, even in the new system, women remained excluded from the benefits of relational capital in the South Korean cinematic field, and they could only find their place as directors by demonstrating exceptional individual abilities.